Wpływ ojców Kościoła na prawosławne pojęcie obrazu Bożego - Kucy, Aleksy (Poznańskie Studia Teologiczne, 2016)
The concept of the divine image in the patristic thought has a very rich tradition and a well-developed semantics. In an exegetic interpretation one can find both a broad treatment of this concept and a very narrow one, the objective one. In the strict sense of this word, the Divine Image, on the image of whom was created man, is Christ, the Incarnate Logos, who has fulfilled the eternal, divine intent towards man and towards the whole creation, which was the divinisation and the state when God will be all in all (1 Corinthians 15:28).